Effects of vertical ground motions on seismic vulnerabilities of a continuous track-bridge system of high-speed railway. Issue 115 (December 2018) - Wei, Biao; Zuo, Chengjun; He, Xuhui; Jiang, Lizhong; Wang, Teng
Abstract: A continuous bridge in high-speed railway is close to several known faults in China. Those faults, respectively at different distances from the bridge site, will produce different ground motions with the different ratios of vertical component to the horizontal component at the bridge site. It is necessary to identify the influence of vertical ground motions on the seismic responses and vulnerabilities of the track-bridge system. This paper solved this problem by carrying out an incremental dynamic analysis (IDA) and a further seismic fragility analysis on a widely used continuous bridge in China. The results show that the damage probabilities of most bridge and track components increase along with the increase of vertical part in ground motions. This trend is significant for the sliding layer of track part in the longitudinal direction and the piers of bridge part in any direction, however, insignificant for the bearings of bridge part in any direction. Moreover, this trend is more significant for the track part across the girder gap due to the different seismic responses of adjacent bridges. The seismic design of track-bridge system should rigorously take the vertical part of ground motions into account. Highlights: Seismic damages of track and bridge components increase with vertical ground motions. Effects of vertical ground motions on track components between bridges are complex. Vertical ground motions should be considered for a track-bridge seismic design. A combination of bridge and CRTS II track is reasonable under earthquakes.